Reconciliation and economic justice in South Africa: The role of the Church and Theology - Dolamo, Ramathate Tseka Hosea (Verbum et ecclesia, 2001)
The Church as we understand it, is an alternative community to the State because it has been borne out of the single most important event of the Resurrection of Jesus Christ from the dead (Pannenberg 1972:87). The Church is therefore an institution that does its theology from the christological perspective without doing violence to the other two persons of the Trinity. One important concept that needs to be revisited by the Church through its theology is that of reconciliation with regard to economic justice in South Africa. We have achieved democracy in April 1994, but economic justice will remain an elusive goal, if reconciliation is not related to South Africa's historical socio-economic imbalances. The Church by its nature, must remain a beacon of hope for those who are struggling from the underside and margins of society.